2020
DOI: 10.1111/jjns.12366
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters and quality of life among patients with chronic heart failure: A cross‐sectional study

Abstract: AimThis study aimed to identify symptom clusters among patients with chronic heart failure (HF) and examine their independent relationships with quality of life (QoL).MethodsA descriptive cross‐sectional design was adopted, and 201 Chinese participants were recruited. Their symptom profiles and QoL were assessed using the Memorial Symptom Assessment Scale‐Heart Failure and Minnesota Living with Heart Failure Questionnaire. Exploratory factor analysis was used to identify the symptom clusters. Pearson's correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Four studies detected the impact of the dyspnoeic symptom cluster on HRQoL ( n = 2), re‐hospitalization and/or mortality ( n = 2). Two cross‐sectional studies consistently identified the moderate association between higher distress in the dyspnoeic symptom cluster and poorer HRQoL among hospitalized HF patients (Hu et al, 2020; Yi et al, 2018). Among these studies, the one which predominately recruited advanced HF patients (91.1%) showed even more prominent impact of dyspnoeic symptom cluster (Yi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies detected the impact of the dyspnoeic symptom cluster on HRQoL ( n = 2), re‐hospitalization and/or mortality ( n = 2). Two cross‐sectional studies consistently identified the moderate association between higher distress in the dyspnoeic symptom cluster and poorer HRQoL among hospitalized HF patients (Hu et al, 2020; Yi et al, 2018). Among these studies, the one which predominately recruited advanced HF patients (91.1%) showed even more prominent impact of dyspnoeic symptom cluster (Yi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 13 articles corresponding to 12 studies were included in the review (Denfeld et al, 2020;Herr et al, 2015;Hertzog et al, 2010;Hu et al, 2020;Huang et al, 2018;Lee et al, 2014;Lee et al, 2010;Salyer et al, 2019;Smith et al, 2009;Son & Won, 2018;Song et al, 2010;Yi et al, 2018;Yu et al, 2016).…”
Section: Search Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only do clinical manifestations of this disease (i.e. shortness of breath, limb swelling, and decreased tolerance to activities of daily living associated with the chronic nature of the disease) negatively affect the biological, social, economic, and psychological dimensions of patients' lives [ 7 ] and drain the financial sources of healthcare systems [ 8 ], but also they can considerably lower patients' Quality of Life (QOL) [ 9 ]. In this regard, poor QOL leads to prolonged length of hospital stay, increases the mortality rate, and imposes high costs to the health system, patients, and their families.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, QOL is one of the concepts closely related to nursing and nurses have always striven to improve the patients' QOL through the provision of health care and participation in nursing research projects [ 17 ]. Despite that medical advances have improved patients' health outcomes, nurses still have to play their particular roles alongside [ 8 ].…”
Section: Introductionmentioning
confidence: 99%